Modeling the urbanization rate associated with renewable in electricity production and CO2 emissions: a threshold regression approach - Ala’ Bashayreh; Hatem Al-Hindawi; Abla Tahtamouni (Discover Sustainability, 2024)
Abstract The paper analyzes the relationship between urbanization rates, the growing reliance on renewable electricity production, and CO2 emissions per capita. It further examines the economic impact of these urbanization and renewable electricity production variables on GDP per capita using threshold regression and annual data from Jordan covering the period from 1990 to 2022. The objective is to determine whether Jordan can reduce CO2 emissions despite high urbanization rates by increasing the share of renewable energy in electricity production. The fundamental assumption is that the relationship between CO2 emissions and urbanization rates varies according to the share of renewable energy production. Results from the estimated threshold regression model indicate a decline in CO2 emissions per capita during the period from 2004 to 2018, when urbanization rates ranged between 0.78 and 0.91. During this time, the compound growth rate of renewable energy share in electricity production was 24% in regime 2 (2004–2018). In contrast, CO2 emissions per capita increased both before and after this period, suggesting a nonlinear relationship between urbanization rates and CO2 emissions. This nonlinearity implies that Jordan can manage the conflicting goals of the Sustainable Development Goals (SDGs)—sustainable urbanization and low CO2 emissions—by enhancing the share of renewables in electricity production. Additionally, the results demonstrate a positive effect of urbanization rates and renewable energy shares on economic growth.